THE PICTURES OF TEACHERS’ VERBAL AND NONVERBAL IMMEDIACY BEHAVIORS IN EFL CLASSROOM PRACTICES - Maemuna Muhayyang; Ainun Nurdzizati; Asriati Asriati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study investigates the ways of English teachers performing verbal and nonverbal immediacy behaviors to boost the students’ learning motivation in EFL classroom context. Using a descriptive qualitative design, data were collected through nonparticipant classroom observations of two English teachers at SMAN 22 Makassar. An observation checklist and field notes were used to identify patterns of verbal and nonverbal immediacy based on established immediacy frameworks. The findings show that teachers actively used various verbal behaviors, namely inviting students to speak, providing positive feedback, addressing students by name, using humor, showing concern, employing inclusive pronouns, and engaging in self-disclosure. Nonverbal behaviors such as physical proximity, supportive gestures, eye contact, facial expressions, teacher movement, and vocal variety were also consistently demonstrated. These behaviors were strategically applied to build rapport, sustain attention, and create a supportive classroom atmosphere. Overall, the study highlights that verbal and nonverbal immediacy play a crucial role in fostering students’ motivation in the Indonesian EFL context and underscores the importance of teachers being intentional and culturally sensitive in applying immediacy strategies.